Indeterminacy : Waste, Value, and the Imagination. - Alexander, Catherine (WYSE Series in Social Anthropology Ser., 2018)
What happens to people, places and objects that do not fit the ordering regimes and progressive narratives of modernity? Conventional understandings imply that progress leaves such things behind, and excludes them as though they were valueless waste. This volume uses the concept of indeterminacy to explore how conditions of exclusion and abandonment may give rise to new values, as well as to states of despair and alienation. Drawing upon ethnographic research about a wide variety of contexts, the chapters here explore how indeterminacy is created and experienced in relationship to projects of classification and progress.